Efeito de solvente sobre as propriedades ópticas não-lineares de Chalconas e análogos - (:unkn) unknown (Universidade Estadual de Goiás, 2014)
A class of organic molecules that possesses conjugated bridges associated with a Donor-Acceptor group, and that exhibits nonlinear optics potential of second and third order are chalcones, which is defined as α, β unsaturated ketones where both carbonyl and olefinic groups are attached to the aromatic ring. Chalcones have many isolating studies, identification and biological propertis investigation and also have a wide application range in fotonics and medicine. Due to its exceptional electrical properties they have been investigated in photonics field, for instance, in nonlinear optics. Regarding its importance, in this work, we studied chalcones electrical properties in gas phase and in different solvent moieties. We used Hartree-Fock (HF) method, Density Functional Theory (DFT) and Møller-Plesset Perturbation Theory of second order (MP2) using 6-31+G(d) basis set for electronic structure description. The solvente effects were generated by means of Polarizable Continuum Model (PCM) and the electrical properties calculations were carried out employing Finite Field and Couple Perturbed Hartree-Fock methods.
Keywords: Chalconas; Efeito do solvente; Propriedades elétricas; Chalcones; Solvent effect; Electrical properties; CIENCIAS EXATAS E DA TERRA::QUIMICA; QUIMICA::FISICO-QUIMICA